Pengaruh Business Risk, Investment Opportunity Set, dan Sustainability Report Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening - Tiara Kusuma Wardani; Nera Marinda Machdar (Institut Nalanda, 2023)
This research aims to analyzze the influence of business risk, investment opportunity set and sustainability reporting on company value with profitability as a moderator. The population in this research is all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2015-2022. Sample selection method using purposive sampling method. This type of research is qualitative and the type of data used is secondary data. Research results show that Business Risk has a positive effect on company value; Investment Opportunity Set has a positive effect on company value; Sustainabilitu Reporting has a positive effect on company value ; Business Risk has a positive effect on profitability Investment Opportunity set has a positive effect on profitability; sustainability reporting has a positive effect on profitabilitu can mediate the influence of the Investment Opportunitu Set on the value of the company; Profitability can mediate the influence of sustainability reporting on company value.